HUBUNGAN KOMPETENSI KEPRIBADIAN GURU PENDIDIKAN AGAMA ISLĀM MENURUT PERSPEKTIF SISWA DENGAN PENGAMALAN AJARAN AGAMA SISWA DI SMA AL-MA'SOEM - Karima, Nurul Ihsan (2017)
Penelitian ini dilatarbelakangi adanya UU. No.14 Tahun 2005 tentang kompetensi guru yang salah satunya adalah kompetensi kepribadian. Kompetensi tersebut sangat penting dimiliki oleh seorang guru PAI dalam perannya sebagai teladan, mengingat minimnya pengamalan ajaran agama Islām di kalangan siswa. Padahal, mata pelajaran PAI diajarkan untuk diamalkan. Penelitian terdiri dari variabel X dan Y dengan tujuan untuk mengetahui hubungan antara kompetensi kepribadian guru pendidikan agama Islām menurut perspektif siswa dengan pengamalan ajaran agama siswa di SMA Al-Ma'soem yang menggunakan desain korelasi, metode deskriptif, pendekatan kuantitatif, dengan instrumen angket yang disebarkan kepada 243 siswa. Hasilnya menunjukkan bahwa kompetensi kepribadian guru-guru di SMA Al-Ma'soem menurut perspektif siswa berada pada kategori tinggi sebesar 90,95%. Demikian halnya pengamalan ajaran agamanya berada pada kategori tinggi sebesar 83,54%. Hasil analisis product moment menunjukkan bahwa terdapat hubungan antara keduanya dalam kategori sedang sebesar 0,464 dengan model persamaan regresi Y=59,503+0,513x. Artinya semakin meningkat kompetensi kepribadian guru PAI, maka semakin meningkat pula pengamalan ajaran agama siswa dengan peningkatan sebesar 0,513. Besaran pengaruh yang diberikan oleh kompetensi guru terhadap pengamalan ajaran agama siswa sebagai hasil analisis koefisien determinasi adalah 21,5%. Bagi peneliti selanjutnya untuk meneliti faktor-faktor lain yang mempengaruhi pengamalan ajaran agama siswa. ;--- This study is conducted based on the Act No.14 of 2005 on teacher competenciesin which one of those competencies is personality competence. In particular, this competence is very important to be possessed by Islamic Education teachers in their roles as a model due to the lack of Islamicteaching practices among students. In fact, the Islamic Education subjectis taught to be practiced. This study which consisted of the variable x and y aim edatinvestigating the correlation between personality competence of Islāmic education teachersbased on students' perspectivesand the religious teaching practices of students in SMA Al-Ma'some. Therefore, this study employed correlation design, descriptive method, quantitative approach, and the use of questionnaires spread out to 243 students. The results showed that the teacher personality competencies in SMA Al-Ma'soem based on students' perspective were classified in the high category, about 90.95%. Similarly, the religious teaching practiceswere classified in the high category, around 83.54%. The results of product moment analysis showed that there was a correlation between teacher personality competencies and religious teaching practices in the medium category of 0.464 with regression equation model Y = 59,503 + 0,513x. These results indicated that as the Islāmic education teacher personality competencies increased, the religious teaching practices of the students also underwent an increase in the number of 0.513. The magnitude of the influence given by the teachers' personality competence on the students' religious teaching practices as the results of coefficient of determination analysis was 21.5%. Then, for further study, it is also important to examine other factors that influence the religious teaching practices of students.